Where is the green sheep? - Fox, Mem, 1946-; Horacek, Judy (Boston : Sandpiper, 2004)
A story about many different sheep, and one that seems to be missing.
1.7
K-3.
K-3
Keywords: Oversize books -- Specimens; Reading (Elementary); Oversize books; Sheep -- Fiction; Stories in rhyme; Big books; Sheep -- Fiction; Stories in rhyme